2014
DOI: 10.1016/j.cbpa.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of adrenocortical function in captive Nile crocodiles (Crocodylus niloticus)

Abstract: Abstract:The occurrence of stress-inducing factors in captive crocodilians is a concern, since chronic stress can negatively affect animal health and reproduction, and hence production. Monitoring stress in wild crocodiles could also be beneficial for assessing the state of health in populations which are potentially threatened by environmental pollution. In both cases, a noninvasive approach to assess adrenocortical function as a measure of stress would be 2 preferable, as animals are not disturbed during sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 38 publications
2
41
0
Order By: Relevance
“…Steroid hormones may be metabolised and excreted differently between sexes of the same species, resulting in differences in metabolite composition within the faeces (Touma et al, 2003(Touma et al, , 2004. Further, a number of studies demonstrated sex-related differences in fGCM concentrations in response to ACTH administration (Ganswindt et al, 2012(Ganswindt et al, , 2014LeRoux et al, 2016). For example, glucocorticoid levels in females can be affected by the oestrus cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Steroid hormones may be metabolised and excreted differently between sexes of the same species, resulting in differences in metabolite composition within the faeces (Touma et al, 2003(Touma et al, , 2004. Further, a number of studies demonstrated sex-related differences in fGCM concentrations in response to ACTH administration (Ganswindt et al, 2012(Ganswindt et al, , 2014LeRoux et al, 2016). For example, glucocorticoid levels in females can be affected by the oestrus cycle.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the EIA specific responses to the ACTH challenge, we set the sample collected from each individual on the day of ACTH administration as 100% and all other values were expressed as a percentage of the respective value. To compare individual fGCM concentrations in the captive group, individual baseline levels for the two pet animals were calculated using an iterative process as described (Ganswindt, Myburgh, Cameron, & Ganswindt, ). Differences in fGCM concentrations between individuals and between groups were determined using a Kruskal‐Wallis One Way Analysis of Variance on Ranks with a post‐hoc pairwise multiple comparison (Dunn's Test) to isolate the individuals or groups that differed from the others in SigmaPlot for Windows versions 12.5.…”
Section: Materials/methodsmentioning
confidence: 99%
“…Understanding species-specific differences and individual variability in faecal and urinary defecation rates are important for a number of reasons. Firstly, the infrequent and extended excretion rate of urinary and faecal material in reptiles may complicate data interpretations (Ganswindt et al, 2014). Furthermore, the movement of urine into the cloaca (urodeum) before moving into the intestines, where urinary and faecal material can be excreted in unison (Singer 2003), can further complicate the distinction between matrix-specific retention time and steroid hormone metabolite excretion routes.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…However, some more recent studies attempting to understand the physiological response inherent in reptiles to environmental stressors have already opted for non-invasive hormone monitoring in reptiles, e.g. in Nile crocodiles (Crocodylus niloticus, Ganswindt et al, 2014), the three-toed box turtle (Terrapene carolina triunguis, Rittenhouse et al, 2005), the green anole (Anolis carolinensis, Borgmans et al, 2018) or the green iguana (Iguana iguana, Kalliokoski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%